Afghanistan-Pakistan shared waters : state of the basins - Shah, Muhammad Azeem Ali; Lautze, Jonathan; Meelad, Asadullah (Boston : CAB International, 2023)
"An overview of the three most important Afghanistan-Pakistan River Basins, in collaboration with water professionals and government agencies. Key aspects include water resources, land resources, ecological health, environment, climate change, and the social and economic conditions for sustainable management of these precious resources"--